Aplikasi Beberapa Jenis Pakan Terhadap Laju Pertumbuhan dan Laju Mortalitas Rotifera (Brachionus plicatilis) - Salmia, Efriana; Fahmi, Rizkan; Rahmi, Faidha; Dahri, Anwar Hidayat; Hasri, Iwan (Universitas Gajah Putih, 2022)
The research aims to analyze the effect of different feeding on the growth rate and mortality rate of Rotifers.. This study used a Completely Randomized Design consisting of four treatments and four replications. The treatment was determined based on different feeds namely Spirulina flour (3 g/l), yeast (0,03 g/l), soy fermentation and yeast fermentation (0,06 g/l). The results showed the highest growth rate was in spirulina treatment 3 g/l with an average growth rate of 0.82. The highest mortality rate is found in yeast fermentation treatment at a dose of 0,6 g/l with an average value of 0.86.